The effects of institutional context on critical thinking in the workplace - Shelley C. Mishoe (Adult Education Research Conference, 1995)
The purpose of this research was to identify and describe the critical thinking (CT) skills and dispositional traits that are evident in professional practice. The interrelation and interaction of the essential skills for CT can be described. However, dispositional traits and organizational factors and their collective impact on CT must be considered. The importance of consideration of the context when attempting to explain or facilitate CT in practice is advocated.